Моделирование усилий при сверлении костного материала - Хавин, Валерий Львович; Лавриненко, Игорь Сергеевич; Шергин, Сергей Юрьевич (НТУ "ХПИ", 2017)
Рассмотрен подход к моделированию усилий при сверлении трубчатой кости. Дополнительно к главным составляющим осевого усилия и крутящего момента вычисляются компоненты, связанные с внедрением передней части инструмента в обрабатываемый материал и сопротивлением эвакуации срезанного материала. Для определения главных составляющих усилий используется зависимости для удельной работы разрушения костного материала. Сопротивление эвакуации учитывается моделью гранулированной среды, двигающейся с трением вдоль поверхностей сверла и отверстия. Показано, что модель достоверно отражает рост усилий за счет сопротивления эвакуации срезанного материала.

Going is considered the design of efforts at boring of tubular bone. The main constituents of axial effort and twisting moment are presented as efforts of cutting at power co-operation of cutting edges of drill with the processed material. The additional components of axial effort and twisting moment are related to introduction of forehand of instrument in the processed material and resistance of evacuation of the cut away material from opening. Through penetration of drill through a tubular bone plugs in itself the row of the successive stages of co-operation of instrument with bone material. Amount of material (volume), of the instrument cut away for one turn, determined on the basis of the schematized geometry of the cut away volumes. The volume of the cut away material for one turn of instrument is determined as dependence on speed of axial serve on a turn and geometries of cutting part of instrument The model of the pressed element shaving from bone material is presented as an array of granular environment, moving in the conditions of presence resistance (friction) along the surfaces of evacuation ditches of drill and opening surface like the process of extrusion of some polymers. Comparison of results upon settlement of axial effort and twisting moment with experimental data showed that the offered model for certain reflected the height of axial effort at presence of resistance of evacuation of the cut away material. A model allows more exactly to forecast the size of efforts both in initial and eventual phases of boring process and in the phase of the stationary boring.
Modeling of efforts at drilling bone material
Keywords: сверлениe; трубчатая кость; осевое усилие; крутящий момент; удельная работа разрушения; усилия сопротивления эвакуации; boring; tubular bone; axial effort; twisting moment; specific work of destruction; effort of resistance of evacuation